GC-MS analysis, evaluation of phytochemicals, anti-oxidant, thrombolytic and anti-inflammatory activities of Exacum bicolor (Bangladesh Journal of Pharmacology, 2015)
The aim of the present study was to investigate the GC-MS analysis, phytochemical screening, anti-oxidant, thrombolytic and anti-inflammatory activities of methanol extract of leaves of Exacum bicolor. FTIR analysis confirmed the presence of alcohol, phenols, alkanes, aromatic compounds, aldehyde and ethers. GC-MS analysis revealed the presence of eight phyto-constituents. The total phenol, flavonoid and alkaloid contents were 18.0 ± 0.2 mg/GAE/g, 13.1 ± 0.4 mg QE/g and 108.0 ± 1.2 mg AE/g respectively. The DPPH assay exhibited potent anti-oxidant abilities with IC50 8.8 µg/mL. Significant thrombolytic activity was demonstrated by clot lysis method (45.1 ± 0.8%). The methanol extract showed significant membrane stabilization on human red blood cell with IC50 value of 37.4 µg/mL. There was a significant correlation (R2>0.98) with total phenolic content versus anti-oxidant and anti-inflammatory activity. The above results confirmed that E. bicolor could be a promising anti-oxidant, thrombolytic and anti-inflammatory agent.